2022
DOI: 10.1371/journal.pgph.0000526
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of standard HIV testing services delivery to injured persons seeking emergency care in Nairobi, Kenya: A prospective observational study

Abstract: Emergency departments (EDs) in Africa are contact points for key groups for HIV testing services (HTS) but understanding of ED-testing delivery is limited which may impeded program impacts. This study evaluated the offering and uptake of standard HTS among injured persons seeking ED care at Kenyatta National Hospital (KNH) in Nairobi, Kenya. An ED population of adult injured persons was prospectively enrolled (1 March—25 May 2021) and followed through ED disposition. Participants requiring admission were follo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Prior data from the study setting demonstrated that 5.6% of injured patients completed ED-HIV testing. 25 To be able to identify a 10% absolute increase in the proportion of injured patients completing testing, a sample size of >175 participant per assessment period was need (80% power, alpha <0.05). 47 Descriptive analyses were performed for systems level and participant level data using frequencies with percentages or medians with associated interquartile ranges (IQR) as appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior data from the study setting demonstrated that 5.6% of injured patients completed ED-HIV testing. 25 To be able to identify a 10% absolute increase in the proportion of injured patients completing testing, a sample size of >175 participant per assessment period was need (80% power, alpha <0.05). 47 Descriptive analyses were performed for systems level and participant level data using frequencies with percentages or medians with associated interquartile ranges (IQR) as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Prior data from the study setting demonstrated that 5.6% of injured patients completed ED-HIV testing. 25 To be able to identify a 10% absolute increase in the proportion of injured patients completing testing, a sample size of > 175 participant per assessment period was need (80% power, alpha <0.05). 47…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is an a priori exploratory secondary analysis of data from a prospective evaluation of the delivery of standard HTS to injured persons seeking emergency care at Kenyatta National Hospital (KNH) [ 18 ]. KNH, located in Nairobi, is the largest public health centre in Kenya.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally prior work in Western Kenya has found the HIV-positivity rate to be 22.7% in an ED setting [ 17 ]. A 2021 study from Nairobi of ED-based HIV-testing found a prevalence of infection of 11.4% among a cohort of predominately male-injured patients, a prevalence of disease twofold higher than the general population, illustrating the high-risk HIV profile among the ED patients [ 18 ]. The provision of HIVST kits from EDs in high-income settings has been shown to be acceptable to patients and successful in increasing HIV testing but data from populations in Africa at high risk for HIV have not been established [ 6 , 19 ].…”
Section: Introductionmentioning
confidence: 99%